Kepastian Hukum Mengenai Jangka Waktu Sebagai Tersangka Dalam Proses Penyidikan Di Indonesia - Juan Ivander Christian (Darma Cendika Catholic University, 2018)
The Indonesian state is the rule of law as stipulated in the provisions of Article 1 paragraph (3) of the 1945 Constitution of the Republic of Indonesian. The system of government and law enforcement must be carried out based on laws and regulations, Law number 8 of 1981 concerning the book criminal procedural law (KUHAP) as a guideline for the enforcement of material law. The suspect has a set of rights stipulated in the Criminal Procedure Code, based on the provisions of Article 50 paragraph (1) of the Criminal Procedure Code that the suspect has the right to immediately get an examination by the investigator and can then be submitted to the public prosecutor. KUHAP as a guideline for material law enforcement does not regulate the period of investigation and does not regulate legal protection that can be given to suspects whose cases are not delegated in the prosecution process and are not given a warrant for termination of investigation so as not to provide legal certainty. In several respects, the Law on Human Rights Courts and Regulation of the Head of the National Police of the Republic of Indonesian number 12 of 2009 concerning the supervision and control of handling criminal cases within the Indonesian police has regulated the period of investigation. The Human Rights Court Law cannot be applied in all criminal acts in Indonesian but only specifically can be applied in gross human rights violations, while the head of the Indonesian republic's police regulations do not clearly stipulate how long the extension can be carried out and the regulations above apply only in space scope of the police, while Officials of Civil Servants are also included in the investigator. And these regulations are not included in the hierarchy of laws and regulations in Indonesian.